The Mercurio Peruano of the XVIII century: Society of country lovers and the enlightenment press - Ojeda, Rafael (2015)
During the last decade of the XVIII century, four periodic publications came together in the Peruvian capital: the Diario de Lima, the Mercurio Peruano, the Semanario Crítico and the Gaceta de Lima. Of these, has been the Mercurio Peruano, spokesman of the Academic Society of country lovers, the most representative newspaper of dimensions that was reaching the spirit of Enlightenment in our country, turning into the channeler source, par excellence, of first effects of national and modernist identity constitution, managed for Peru.